2018
DOI: 10.3389/fimmu.2018.02479
|View full text |Cite
|
Sign up to set email alerts
|

TRIM21 Restricts Coxsackievirus B3 Replication, Cardiac and Pancreatic Injury via Interacting With MAVS and Positively Regulating IRF3-Mediated Type-I Interferon Production

Abstract: Tripartite motif-containing 21 (TRIM21) is a regulator of tissue inflammation and pro-inflammatory cytokine production, and has been implicated in negative regulation of IRF3-dependent type I interferon signaling. However, the antiviral activity of TRIM21 varies among diverse viruses and its role on regulation of type I interferon remains inconsistent in different microbial infections. Here, we investigate the potential role for TRIM21 in controlling Coxsackievirus B3 (CVB3) replication and susceptible organ p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
48
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(49 citation statements)
references
References 37 publications
0
48
1
Order By: Relevance
“…Aside from the prototypical K63 and K48 ubiquitin linkages, other chain types can also be critical in certain situations. For example, in addition to its role in autophagy, K27-linked polyubiquitin mediates the recruitment of MAVS to TBK1, leading to IRF3 activation and IFN-I production in response to viral infection [95,96]. Upon infection with several viruses including HCV, Newcastle disease virus (NDV), SeV, VSV and Coxsackie virus B3 (CVB3), TRIM21 is expressed and interacts with MAVS through its PRY-SPRY domain.…”
Section: Antiviral Immune Signalling By Trimsmentioning
confidence: 99%
See 1 more Smart Citation
“…Aside from the prototypical K63 and K48 ubiquitin linkages, other chain types can also be critical in certain situations. For example, in addition to its role in autophagy, K27-linked polyubiquitin mediates the recruitment of MAVS to TBK1, leading to IRF3 activation and IFN-I production in response to viral infection [95,96]. Upon infection with several viruses including HCV, Newcastle disease virus (NDV), SeV, VSV and Coxsackie virus B3 (CVB3), TRIM21 is expressed and interacts with MAVS through its PRY-SPRY domain.…”
Section: Antiviral Immune Signalling By Trimsmentioning
confidence: 99%
“…Upon infection with several viruses including HCV, Newcastle disease virus (NDV), SeV, VSV and Coxsackie virus B3 (CVB3), TRIM21 is expressed and interacts with MAVS through its PRY-SPRY domain. This association allows for the conjugation of K27-linked polyubiquitin onto the K325 residue of MAVS for downstream signalling [95,96].…”
Section: Antiviral Immune Signalling By Trimsmentioning
confidence: 99%
“…In fact, consistently elevated IL-6 levels were observed in an EV-A71 infection neonatal mouse model resulting in severe damage to numerous organs including the brain (Khong et al, 2012) pointing to EV infected astrocytes as contributors to CNS damage. Indeed, previous studies found elevated levels of IL-6 and IL-8 in CSF of EV-A71 positive patients with encephalitis or meningoencephalitis Liu et al, 2018) and expression of these cytokines may be due to viral infected astrocytes. In one study, CVB3 infection of astrocytoma cells resulted in a productive but non-cytopathic infection that could contribute to viral persistence in vivo within the CNS.…”
Section: Innate Immune Response and Enterovirus Countermeasuresmentioning
confidence: 91%
“…Other enteroviruses including CVB1, CVB5, EV-A71 and CVA16 induced type I IFNs through activation of TLR7 (Chehadeh and Alkhabbaz, 2013;Song et al, 2018). Further study of CVB3 infection revealed the upregulation of TRIM21, an intracellular protein that directs virions for degradation, which was necessary in mediating type I IFN (IFNβ) antiviral response through IRF3 (Liu et al, 2018). Viral spread to other tissues was observed in TRIM21 deficient mice, but the importance of this in terms of neuroinvasion remains unexplored (Liu et al, 2018).…”
Section: Innate Immune Response and Enterovirus Countermeasuresmentioning
confidence: 99%
See 1 more Smart Citation